Proceedings of the 14th ACM / IEEE International Symposium on Empirical Software Engineering and Measurement (ESEM) 2020
DOI: 10.1145/3382494.3410671
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on the Interplay between Software Engineering and Systems Engineering during SoS Architecting

Abstract: Background: The Systems Engineering and Software Engineering disciplines are highly intertwined in most modern Systems of Systems (SoS), and particularly so in industries such as defense, transportation, energy and health care. However, the combination of these disciplines during the architecting of SoS seems to be especially challenging; the literature suggests that major integration and operational issues are often linked to ambiguities and gaps between system-level and software-level architectures. Aims: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…A previous study by Cadavid et al [10] already found that mutual assumptions at system-and software-level are a major issue during SoS architecting. In this study, we confirmed this insight, discovering that, in large scale systems, assumptions on the dynamic behavioral aspects of software-intensive subsystems such as the ones related to time are, indirectly, a major cause of budget, integration and operation-related problems.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A previous study by Cadavid et al [10] already found that mutual assumptions at system-and software-level are a major issue during SoS architecting. In this study, we confirmed this insight, discovering that, in large scale systems, assumptions on the dynamic behavioral aspects of software-intensive subsystems such as the ones related to time are, indirectly, a major cause of budget, integration and operation-related problems.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the negative impact of insufficient emphasis on the dynamic (behavioral) elements of the sub-systems, and the communication challenges in multidisciplinary engineering teams (cf. [10], [5]) highlight the importance of proper approaches for specifying said dynamic behavior.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations